Biorthogonal Systems Approximating the Solution of the Nonlinear Volterra Integro-Differential Equation. (5th July 2010) - Berenguer, M. I.; Garralda-Guillem, A. I.; Ruiz Galán, M.
Abstract : This paper deals with obtaining a numerical method in order to approximate the solution of the nonlinear Volterra integro-differential equation. We define, following a fixed-point approach, a sequence of functions which approximate the solution of this type of equation, due to some properties of certain biorthogonal systems for the Banach spacesC [ 0, 1 ] andC [ 0, 1 ] 2 .